Role of physical activity, physical fitness, and chronic health conditions on the physical independence of community-dwelling older adults over a 5-year period. (July 2016) - Pereira, Catarina; Baptista, Fátima; Cruz-Ferreira, Ana
Highlights: Older adult may improve their physical independence up to 8% over 5-years. This corresponds to regain the ability to perform 1 or 2 activities of daily living. Increasing walking, agility, and aerobic endurance improves physical independence. Low co-morbidities (initial and over time) protects physical independence. High initial physical independence is by itself protective against future dependence. Abstract: The variability in the individual characteristics and habits could help determine how older adults maintain independence. The impact of the variability in physical activity, physical fitness, body composition, and chronic health conditions (co-morbidities) on the independence of older adults, especially over time, is seldom examined. This study aims to analyze quantitatively the impact of baseline values and changes in physical activity, physical fitness, body composition, and co-morbidities on the physical independence of community-dwelling, older adults over a 5-year period. Data from 106 and 85 community-dwelling adults (≥60 years) were collected at baseline and after five years, respectively. Linear regression selected the main predictors of changes in physical independence as follows: the baseline physical independence ( β  = 0.032, R 2  = 9.9%) and co-morbidities ( β  = −0.191, R 2  = 6.3%) and the changes in co-morbidities ( β  = −0.244, R 2  = 10.8%), agility ( β  = −0.288, R 2  = 6.7%), aerobic endurance ( β  = 0.007, R 2  = 3.2%), and walking expenditure ( β  = 0.001, R 2  = 5.1%) ( p  < 0.05). In conclusion, baseline physical independence, baseline co-morbidities, and changes in co-morbidities, walking, agility, and aerobic endurance predicted physical independence over five years regardless of age and gender. Gains of up to 8.3% in physical independence were associated with improvements in these variables, which corresponds to regaining independence for performing one or two activities of daily living.